Plasmonic gold nanodiscs fabricated into a photonic-crystal nanocavity. (26th April 2016) - Sediq, Khalid N; Coles, David; Fry, Paul W; Lidzey, David G
Abstract: We fabricate and characterise an optical structure consisting of a photonic crystal L3 nanocavity containing two gold nanodisks placed close to a field antinode. We use finite difference time domain (FDTD) modelling to show that the optical properties of the nanocavity are sensitive to the physical separation between the gold nanodisks, and that at reduced separation, the q -factor of a cavity mode polarised parallel to the dimer long-axis is reduced, indicating coupling between the cavity mode and a localised plasmon. Preliminary experimental measurements indeed indicate a damping of the cavity mode in the presence of the dimer; a result consistent with the FDTD modelling. Such a scheme may be used to integrate plasmonic systems into all-optical photonic circuits.